The Cu-68m/Cu-68 isotope as a new probe for hyperfine studies: The nuclear moments - Fenta, A. S. (2017)
Time Differential Perturbed Angular Correlation of gamma-rays (TDPAC) experiments were performed for the first time in the decay of Cu-68m (6(-), 721 keV, 3.75 min) produced at the ISOLDE facility at CERN. Due to the short half-life of the source isotope, the measurements were carried out online. The intermediate state (2(+), 84.1 keV, 7.84 ns) offers the unique opportunity to study the electromagnetic fields acting at a copper probe in condensed matter via hyperfine interactions. The present work allowed determination of the nuclear moments for this state. The electric quadrupole moment vertical bar Q(2(+), 84.1 keV)vertical bar = 0.110(3) b was obtained from an experiment performed in Cu2O and the magnetic dipole moment vertical bar mu vertical bar = 2.857(6) mu(N) from measurements in cobalt and nickel foils. The results are discussed in the framework of shell model calculations and the additivity rule for nuclear moments with respect to the robustness of the N = 40 sub-shell. Copyright (C) EPLA, 2016